Effects of increased eccentric loading on bench press 1RM - Doan, B. K.; Newton, R. I.; Marsit, J. L.; Triplett-McBride, N. T.; Koziris, L. P.; Fry, A. C.; Kraemer, W. J. (The Journal of Strength and Conditioning Research, 2002)
The purpose of this study was to measure the effects of additional eccentric loading on subsequent concentric strength. Eight subjects with some experience in weight training volunteered to perform maximal attempts in the barbell bench press using detaching hooks that allowed them to lower 105% of their concentric 1 repetition maximum (RM) and raise 100%. The detaching hooks allowed attachment of extra weight to the bar and would release from the bar at the bottom of the lift, reducing the weight lifted during the concentric phase of the lift. After determining their 1RM for the bench press, the subjects attempted to increase their performance by using a heavier eccentric load with the detaching hooks. All 8 subjects who completed the study increased their 1RMs by 5 to 15 pounds. The use of additional eccentric loading significantly (p = 0.008) increased the weight that could be lifted on the subsequent concentric phase and therefore 1RM performance. This phenomenon was a result of the enhancement of stretch-shortening cycle performance by the increased eccentric load. Athletes who are interested in developing 1RM strength in the bench press may benefit from the use of additional eccentric loading.